Preliminary Results of Wood Endophytes of Abies cilicica in Yenisarbademli of Isparta Province - Lehtijarvi, A.; Dogmus-Lehtijzarvi, H. T.; Kaya, A. G. Aday; Oskay, F. (Kastamonu Univ, Orman Fak, 2012)
Fungal colonisation originating from endophytic thalli in wood of healthy Taurus fir (Abies cilicica) was studied. Bore cores were taken from living trees during field surveys. The bore cores were cut into 0.5 cm long fragments, washed with 70% (v/v) ethanol, flamed and placed into petri dishes containing malt extract, agar and streptomycin. The plates were incubated at 25 degrees C for 4 weeks. The outgrowing mycelia were pure-cultured and identified based on amplification and sequencing of the internal transcribed spacer (ITS) region of their nuclear ribosomal DNA. Totally 12 different fungal species were isolated from Abies cilicica wood cores. Five of them belong to Basidiomycetes. The present study is the first investigation of endophytic wood fungi occurring in fir in Turkey using DNA-based methods. Therefore the study is expected to provide new information of the pioneering colonizers of wood tissues in stems of living Taurus firs.
Keywords: Abies cilicica; wood tissue; endophyte; Basidiomycetes